2019
DOI: 10.1097/md.0000000000014113
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns and Helicobacter pylori infection in a group of Chinese adults ages between 45 and 59 years old

Abstract: Limited studies have reported the association between dietary patterns and the risk of Helicobacter pylori (H pylori) infection. The purpose of this study was to evaluate the relationship between dietary patterns and H pylori infection in a Chinese population ages from 45 to 59 years. We performed a cross-sectional examination of the associations between dietary patterns and H pylori infection in 3014 Chinese adults ages between 45 and 59 years from Hangzhou city, Zhejiang province, China. Dietary intake was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 32 publications
0
22
2
Order By: Relevance
“…8 Altogether 24 471 adult subjects, aged 16 years or older (mean age 51.7 years), having visited a healthcare center or an outpatient medical clinic for a routine health examination during the study period, were enrolled and investigated by means of upper endoscopy and serology (anti-H pylori IgG); data on behavioral factors and previous medical history were collected by using a questionnaire. 10 In 3252 subjects without previous history of H pylori eradication, the prevalence of the infection was 27.5%. During the most recent years (2016-2017), 23% of the study population reported previous eradication therapy; this was higher than in subjects recruited within the previous periods (13.9% in 2005 and 19.3% in 2011).…”
Section: Other Prevalence Studies In the General Populationmentioning
confidence: 99%
See 3 more Smart Citations
“…8 Altogether 24 471 adult subjects, aged 16 years or older (mean age 51.7 years), having visited a healthcare center or an outpatient medical clinic for a routine health examination during the study period, were enrolled and investigated by means of upper endoscopy and serology (anti-H pylori IgG); data on behavioral factors and previous medical history were collected by using a questionnaire. 10 In 3252 subjects without previous history of H pylori eradication, the prevalence of the infection was 27.5%. During the most recent years (2016-2017), 23% of the study population reported previous eradication therapy; this was higher than in subjects recruited within the previous periods (13.9% in 2005 and 19.3% in 2011).…”
Section: Other Prevalence Studies In the General Populationmentioning
confidence: 99%
“…9 A prevalence study on 45-and 59-year-old individuals residing in Zhejiang Province in East China and attending annual health examinations was performed in 2015-2016. 10 In 3252 subjects without previous history of H pylori eradication, the prevalence of the infection was 27.5%. However, the study participants were recruited in the capital of the province where the income and educational level are higher than in the general population; this could explain the lower H pylori prevalence rates compared to previously reported prevalence rates in China.…”
Section: Other Prevalence Studies In the General Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…Physical activity was assessed using the International Physical Activity Questionnaire (IPAQ), and expressed as metabolic equivalent hours per week(MET-h/week) [29]. Then, based on MET-h/week, three categories of physical activity were assigned, including light, moderate and heavy [30].Additional information including smoking habits (never, current, and former smokers), education level(primary school or below, middle and high school, junior college or above) was recorded with a structured questionnaire. Moreover, total energy intake was estimated through this semi-quantitative FFQ, and results were expressed in kilocalorie per day (kcal/day) and categorized according to quartile.…”
Section: Assessment Of Other Variablesmentioning
confidence: 99%